2013
DOI: 10.1117/12.2017209
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence characteristics of flat optical fiber in radiation dosimetry under different electron irradiation conditions

Abstract: The thermoluminescence (TL) provided by flat optical fibers (FF) have been proposed as the basis for a novel radiation sensor, for use in medical dosimetry for both diagnostic and radiotherapy applications. A flat optical fiber with nominal dimensions of (3.226 x 3.417 x 0.980) mm 3 and made of pure silica SiO 2 was selected for this research. The FF was annealed at 400 o C for 1 h before being irradiated. Using a linear accelerator (LINAC), delivering doses in the range 2.0-10.0 Gy, the kinetic parameters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 14 publications
6
18
0
Order By: Relevance
“…6, the activation energy E a of the deconvoluted glow peaks 2 and 4 show a significant decrease, by 30-60% with increasing dose. This result is in accord with the results for pure silica fiber following electron and photon irradiation, as measured by Alawiah et al (2013), the latter observing the dependency of E a on dose. Peaks 1, 3 and 5 were found to increase by 20-50% with increase in dose from 0.1 Gy to 0.7 Gy.…”
Section: Kinetic Parameters Evaluationsupporting
confidence: 93%
See 2 more Smart Citations
“…6, the activation energy E a of the deconvoluted glow peaks 2 and 4 show a significant decrease, by 30-60% with increasing dose. This result is in accord with the results for pure silica fiber following electron and photon irradiation, as measured by Alawiah et al (2013), the latter observing the dependency of E a on dose. Peaks 1, 3 and 5 were found to increase by 20-50% with increase in dose from 0.1 Gy to 0.7 Gy.…”
Section: Kinetic Parameters Evaluationsupporting
confidence: 93%
“…In all cases, the fibers were placed at the center of the field. Detailed description of the sample holder can be found in Alawiah et al (2013). Calibration of the x-ray beams was carried out using a calibrated cavity ionization chamber model PTW Farmer 30004 (Al electrode), the procedure following an internationally recognized calibration protocol (ICRU, 1976).…”
Section: Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researchers had observed that the TL performance of an irradiated optical fibers is influenced by the type of fiber including the type of dopant material, diameter of the fiber core, the shape of fiber and the type of radiation (Hashim et al, 2010;Ramli et al, 2009;Abdul Rahman et al, 2011;Yaakob et al, 2011;Ong et al, 2009;Alawiah et al, 2013Alawiah et al, , 2015.…”
Section: Introductionmentioning
confidence: 97%
“…An additional form of glass based dosimeter that has attracted considerable and growing attention are silica-based optical fibres , offering a range of advantages over other passive dosimeter types. These include high spatial resolution, by virtue of their very small size ( $ 125 mm) relative to many other forms of dosimeter, linear dose response in both the low and high dose regimes (Alawiah et al, 2013a(Alawiah et al, , 2013bGirard et al, 2013), capability for real time remote monitoring (Fernandez et al, 2008;O'Keeffe et al, 2007), lower cost (Espinosa et al, 2006) and relatively high dose sensitivity .…”
Section: Introductionmentioning
confidence: 98%